Penggunaan Model Konseling Kelompok Teknik Role Playing sebagai Upaya Meningkatkan Hubungan Interpersonal Siswa - Delianti, Irfiana; Saman, Abdul; Fitirana, Fitriana (Indonesian Journal of School Counseling: Theory, Application, and Development, 2025)
his research examines the implementation of group counseling services using the role-playing technique to improve students' interpersonal relationships at SMP Negeri 49 Makassar. The main objectives of this research are: (1) To determine the description of the level of interpersonal relationships before and after being given group counseling services using the role-playing technique, (2) To understand how the implementation of group counseling services with the role-playing technique can improve the interpersonal relationships of students at SMPN 49 Makassar, (3) To identify the effect of group counseling services using the role-playing technique on improving students' interpersonal relationships at SMPN 49 Makassar.This research uses a quantitative approach with a quasi-experimental design, specifically the pretest-posttest non-equivalent control group design. Based on calculations using SPSS 20 with an independent t-test, the significance value (2-tailed) was found to be less than 0.05, namely 0.002 < 0.05, indicating that the implementation of group counseling services using the role-playing technique can significantly improve students’ interpersonal relationships